PENGARUH PEMBERIAN REBUSAN DAUN TEH HIJAU TERHADAP PERUBAHAN KADAR KOLESTROL PADA LANSIA DI DESA LOSARI KECAMATAN GONDANG KABUPATEN NGANJUK - Wilda, Lexy Oktora; Damayanti, Ine Nadia (JURNAL SABHANGA, 2022)
Introduction : Cholesterol can cause problems if the levels are excessive. The purpose of this study was to determine the effect of giving boiled green tea leaves to changes in cholesterol levels.